Communication of dental and oral care in patients with anxiety disorders and bipolar patients in private clinics: Autoethnography - Sejati, Irwiena Tahar; Bashabih, Masyitoh; Martha, Evi (International Journal Labs, 2024)
Mental health disorders are characterized by a variety of psychological, social, and emotional factors. Communication is the main gateway as a determinant of effective treatment, successful treatment, and improvement of the patient's quality of life within the scope of health services. This article is a case series written in Benntuk Autoethnography, a scientific writing that pours out the author's personal experience which is considered a social phenomenon that deserves to be researched. This scientific paper helps dentists, specialists in dentistry, and dental nurses better understand how to communicate with patients who have mental health disorders. This study is expected to provide information regarding optimal treatment outcomes and satisfactory care until the quality of dental and oral health services improves.